The use of heart rate variability monitoring for exercise prescription and performance - DeBlauw, J. (Kansas State University, 2021)
Background: Results from predetermined exercise programs are typically variable, with high, low, and non-responders being reported. These mixed results are likely due to a lack of individualized exercise prescription. Exercise prescription may be enhanced in real-time through the use of individual monitoring techniques such as autonomic nervous activity via heart rate variability (HRV) or hormone responses. The use of HRV provides insight into how an individual responds to an exercise training load, offering practitioners and coaches valuable information about the individual`s adaptations to the overall exercise program. The purpose of this dissertation was to examine the relationship between HRV and other current methods of monitoring individual training responses, the efficacy of HRV to guide high intensity functional training, and whether acute alterations in resting HRV might affect performance.